Retrospective analysis of clinical yeast isolates in a hospital in the centre of Portugal: spectrum and revision of the identification procedures - Paulo, Cristiana (2009)
We conducted a four-year (2003-2006) retrospective study of yeasts recovered in a hospital laboratory in the centre of Portugal to evaluate the epidemiology of yeast infections. Clinical isolates and data were gathered from 751 patients corresponding to 906 episodes of yeast infection. The isolates were first identified using classical and commercial methods, routinely employed at the hospital laboratory. We then re-identified the same isolates using RFLP of the ITS 5.8S rRNA gene and sequence of the D1/D2 domain of the 26S rRNA gene. Candida parapsilosis isolates were re-identified using the Ban I digestion of the SADH gene. C. albicans was the most frequently isolated of the yeasts found in the analysed specimens, with an overall incidence of 69.6% and then in deceasing order, C. glabrata, C. tropicalis, C. parapsilosis and C. krusei. C. parapsilosis was most frequently recovered from younger patients, decreasing with age, while C. glabrata occurrence increased with age. We found an increased number of cases of fungemia per 100,000 people per year, reaching a maximum of 4.4 during 2006.